Peran PR PT. Pegadaian (Persero) Kanwil X Bandung dalam Program Corporate Social Responsibility - Safa Camila Rahma Nur Annisa Priono; Sophia Novita (UNISBA Press, 2023)
Abstract. PT. Pegadaian (Persero) is a state-owned company engaged in the pawn business. In carrying out its corporate social responsibility, PT. Pegadaian (Persero) launched The Gade Clean and Gold program